The Thrombogram: Monitoring Thrombin Generation in Platelet Rich Plasma - Hemker, Coenraad H.; Giesen, Peter L. A.; Ramjee, Manoj; Wagenvoord, Rob; Béguin, Suzette (Thrombosis and Haemostasis, 2000)
A method is described in which thrombin activity in clotting plasma can be monitored through the continuous measurement of the fluorescent split-product of the substrate Z-Gly-Gly-Arg-AMC. The signal is not impaired by turbidity; therefore proper measurement is not disturbed by the occurrence of a clot or the presence of platelets and direct measurement in platelet rich plasma is possible.
Keywords: Thrombin generation; thrombin potential; thrombogram; platelet rich plasma